Inferior Outcomes of Fludarabine–Cyclophosphamide–Rituximab Chemotherapy in Korean Chronic Lymphocytic Leukemia Patients with Concurrent Thrombocytopenia and Anemia - Tong-Yoon Kim; Gi-June Min; Young-Woo Jeon; Seung-Ah Yahng; Seok-Goo Cho; Jong-Mi Lee; Myungshin Kim; Ki-Seong Eom (Biomedicines)
Background/Objectives: Anti-CD20 monoclonal antibodies combined with alkylator-based chemotherapy enhance survival in chronic lymphocytic leukemia (CLL). However, the risks of infection and bone marrow suppression may mean that new, targeted therapies are more appropriate for some patients than fludarabine–cyclophosphamide–rituximab (FCR). In the Republic of Korea, where insurance limits coverage to novel agents, FCR therapy should be carefully considered for patients with CLL. Methods: Using clinical data from 144 FCR-treated patients with CLL, we retrospectively analyzed clinical characteristics impacting survival outcomes, the impact of cytopenia after FCR, and the durable remission status in terms of measurable residual disease (MRD). We compared the impact of bicytopenia with those of other hematologic conditions. Results: The 5-year overall survival (OS) and 5-year progression-free survival (PFS) for all patients were 84.4% and 68.3%, respectively. FCR-treated patients in the bicytopenia and TP53-positive groups exhibited poor OS and PFS; in particular, the bicytopenia group often experienced prolonged anemia and thrombocytopenia (6–12 months). The responder group achieved sustained remission for a median of 5 years for MRD negativity. Conclusions: In bicytopenia, FCR can induce prolonged cytopenia, making it difficult to switch to second-line therapy or complete cycles of chemoimmunotherapy, directly affecting poor survival outcomes. The cautious application of FCR therapy in CLL without bicytopenia or TP53 positivity can achieve long-term remission.